Aerosol particle and trace gas emissions from earthworks, road construction, and asphalt paving in Germany: Emission factors and influence on local air quality. (December 2015) - Faber, Peter; Drewnick, Frank; Borrmann, Stephan
Abstract: Aerosol emissions from construction sites have a strong impact on local air quality. The chemical and physical characteristics of particles and trace gases emitted by earthworks (excavation and loading of soil as well as traffic on unpaved roads) and road works (asphalt sawing, smashing, soil compacting, asphalt paving) have therefore been addressed in this study by using a mobile set-up of numerous modern online aerosol and trace gas instruments including a high-resolution aerosol mass spectrometer. Fuel-based emission factors for several variables have been determined, showing that earthwork activities and compacting by use of a plate compactor revealed the highest median emission factors for PM10 (up to 54 g l −1 ). Construction activities were assigned to contribute about 17% (36 000 t a −1 ) to total PM10 emissions and 3% (13 500 t a −1 ) to total traffic-related NOx emissions in Germany. In particular, calculated PM10 emissions by earthworks are about 15 800 t a −1 corresponding to 44% of total PM10 emissions by construction activities in Germany. Mechanical processes such as asphalt sawing (PM1 /PM10  = 18 ± 31%), soil compacting by a plate compactor (PM1 /PM10  = 5 ± 6%) and earthworks (PM1 /PM10  = 2 ± 5%) emit predominantly coarse mineral dust particles. Contrary to that, particle emissions by thermal construction processes (asphalt paving: PM1 /PM10  = 62 ± 14%) and by the internal combustion engines of heavy machinery (e.g. road roller PM1 /PM10  = 94 ± 9%) are mostly in the submicron range. These particles were mainly composed of organics containing non-polar saturated and unsaturated hydrocarbons (e.g. asphalting: O:C < 0.01, H:C = 2.01). Besides construction activities, mineral dust is also emitted over cleared land by wind-driven resuspension depending on wind speed. PM10 emissions by construction activities often result in local concentrations > 100 μg m −3 and can easily breach the European limit level of PM10 . This study also shows that particulate mineral dust emissions are strongly dependent on soil moisture and can thus successfully be reduced to a high percentage by wetting the ground (for PM10 up to 95 ± 34%) showing the importance of potential mitigation strategies. Highlights: Construction site emissions are characterized by modern online techniques. These emissions have significant effects on local air quality. The influence of meteorological conditions on mineral dust emissions is shown. An emission inventory is calculated based on fuel-based emission factors. Construction site emissions contribute to 17% of total PM10 emissions in Germany.